(1.5)³+(4.7)³+(3.8)³-3*1.5*4.7*3.8/(1.5)²+(4.7)²+(3.8)²-1.5*4.7-4.7*3.8-1.5*3.8
Answers
Answered by
3
Let a = 1.5, b = 4.7 and c = 3.8
Then, the given expression is:
\frac{a^3 + b^3 + c^3 - 3abc}{a^2 + b^2 + c^2 - ab - bc - ac}
a
2
+b
2
+c
2
−ab−bc−ac
a
3
+b
3
+c
3
−3abc
Now, a^3 + b^3 + c^3 - 3abc = (a + b + c)(a^2 + b^2 + c^2 - ab - bc - ac)a
3
+b
3
+c
3
−3abc=(a+b+c)(a
2
+b
2
+c
2
−ab−bc−ac)
So, the expression is equivalent to:
a + b + c = 1.5 + 4.7 + 3.8 = 10.0
Answered by
1
Step-by-step explanation:
Please mark me as a brainlist, please
Hope you like the answer,
Take care and goodbye
Attachments:
![](https://hi-static.z-dn.net/files/d1c/bed1a736e8230c3db53e85507e435653.jpeg)
Similar questions